Six long years: exploring resettlement as a durable solution for Rohingya refugees in Bangladesh - Mithun, Mahanam Bhattacharjee (Frontiers in Human Dynamics, 2023)
Rohingya refugees from Myanmar have been living in Bangladesh since the 1970s. Although some successful negotiations with the Myanmar government resulted in repatriation in the 1970s and 1990s some refugees remained in Bangladesh. In 2017, after the large-scale exodus of Rohingya refugees from Myanmar, they have been living in Bangladesh for nearly five years. So far, none of the refugees get a chance to go back to their motherland. This study constitutes an exploratory research endeavour using qualitative research methodologies. This research explores resettlement as a durable solution option and provides a set of recommendations for ensuring the protection and upholding the dignity of refugees. This research argues that any solution options should be based on consultations with the refugee population. The findings of this research also illustrate why resettlement pathways for the vulnerable members of the refugee community should be open to ensure protection and for providing opportunities in a third country in the absence of a viable repatriation process.